Manajemen Perpustakaan Sekolah (Studi pada Perpustakaan Sekolah Alam Insan Mulia Lubuk Linggau) - Dian Bastian; Murni Yanto; Deri Wanto (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2022)
Library management in schools is essentially a stage carried out with the aim of optimizing the overall performance of the existing resources in the library itself which is needed to achieve library goals. Libraries as educational institutions and information provider institutions will have good performance if they are supported by adequate management, so that all institutional activities will lead to efforts to achieve the goals that have been proclaimed. This study aims to describe the process of library management at the Insan Mulia Natural School Lubuk Linggau. The details are to find out how the implementation of management functions carried out in managing the library starts from planning, organizing, actuating, controlling which is carried out in the library of the Insan Mulia Natural School Lubuk Linggau. The method used in this research is using descriptive qualitative research methods to determine the implementation of library management at the Insan Mulia Natural School Lubuk Linggau. This study's subjects were the library's heady, librarians, teachers, and students. The result of this study is that the implementation of management functions in the Alam Insan Mulia Lubuk Linggau school library has been going well.